Experimental observation of backscattered light based on different coherence between incident laser beams - Xiangfu Meng; Chen Wang; Honghai An; Guo Jia; Huazhen Zhou; Sizu Fu (High Power Laser Science and Engineering, 2013)
Recent experimental results on NIF revealed a much higher stimulated Brillouin scattering (SBS) and stimulated Raman scattering (SRS) backscatter than expected; one possible reason was due to the coherence between incident laser beams. In our research, two laser beams (${\sim }1~ns $, ${\sim }250~J , 527~nm $ in each one) with different coherent degrees between them from the SG-II facility were employed to irradiate an Au plate target; the backscatter of SBS and SRS in the range of the given solid angle had been measured. The results showed that it could change dramatically corresponding to the difference of the coherent degree between the two laser beams, and there was usually more intense backscatter the higher the coherent degree between the incident beams.